(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Human conscience – as inner moral court or as the dynamic ability to make decisions – represents the object of education and also its premise. A successful conscience shaping requires the fulfillment of certain conditions which, because of the post-modern context of our society, have become difficult to meet. For this reason, the conscience shaping process today is more than a personal task, becoming a social and political one also, with the purpose of securing a safe social environment.